STUDENTS’ EXPERIENCES ON EXTENSIVE READING THROUGH WATTPAD APPLICATION - Sartika Puspita Sari; Maman Suryaman; Fauzi Miftakh (IKIP Siliwangi, 2023)
The aims of this study was to find out students’ responses regarding the implementation of extensive reading activity through Wattpad application. This study used qualitative research and a case study as research design. The site of the study was one of the senior high school in Karawang, West Java. The articipants was one class of eleven grades consisted of 46 students and six of them were chosen as representatives for interview. The data were collected by observation and semi-structured interview. The data were analyzed using qualitative data analysis by Miles, Huberman & Saldana (2014). Three major findings were found as follows: (1) Extensive reading using Wattpad increase students’ motivation to read, (2) Wattpad is an effective media in reading activity, (3) Students' challenges in extensive reading activity through Wattpad. Keywords: Students’ Experiences; Extensive Reading; Wattpad Application